PENGARUH PEMBERIAN SUPLEMEN KALSIUM DALAM PENCEGAHAN PREEKLAMPSI PADA IBU HAMIL TRIMESTER 2 - Iin Setiawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
During pregnancy, the need for increased calcium intake. Adequate calcium intake can reduce the risk of preeclampsia. the survey results of preliminary studies in Polindes Asemjaran Banyuates over the past three months, Found that three pregnant women detected preeclampsia from a total of 57 pregnant women (5.26%). The purpose of the study to analyze the effectiveness of calcium in pregnant women topreventing preeclampsia in the working area of Polindes Asemjaran Banyuates.The research design used was Quasi Eksperimen with Non Equivalent Control Group approach. The independent variable is Calcium Supplementation and dependence is the Occurrence of Preeclampsi on Trimester 2 Pregnant Woman. The sample of this study is trimester 2 pregnant women who are at risk of experiencing preeclampsia that meet the criteria. The instrument was used the observation sheet, and analyzed using Parametric Test if qualified and non-parameteric test if not qualified with a 0.05.The result of statistical test in both dose group 500 mg and 1000 mg with Paired T-Test was obtained p value (0,941)> α (0,05) in 500 mg dose group and Wilcoxon Signed Rank Test result p value (0,105) > a ( 0.05) at a dose of 1000 mg the meaning is H1 and H2 are rejected, there is no difference before and after given calcium supplement dose 500 mg or 1000 mg to prevent preeclampsi. While in the posttest test with Mann Whitney Test in both groups obtained results p Value (0.105)> α (0.05), it can be concluded that supplementation of calcium dose 500 mg and 1000 mg not effective to prevent preeclampsia.Calcium supplementation of 1000 mg and 500 mg doses has not been proven statistically effective in preventing preeclampsia. Further research is recommended to increase the number of samples, so that the research results will be visible and can be generalized to all pregnant women.